Review. Politeness in the History of English: From the Middle Ages to the Present Day. By Andreas H. Jucker. Cambridge University Press, 2020. Pp. 210. - Rogos-Hebda, Anna (Studia Anglica Posnaniensia, 2021)
Review. Politeness in the History of English: From the Middle Ages to the Present Day. By Andreas H. Jucker. Cambridge University Press, 2020. Pp. 210.